2012
DOI: 10.1179/1077352512z.00000000021
|View full text |Cite
|
Sign up to set email alerts
|

An updated review on asbestos and related diseases in China

Abstract: Government policies to prevent ARD have been implemented but more actions are necessary to ensure compliance and ultimately, the complete elimination of asbestos to prevent a heavy future disease burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 21 publications
0
29
0
Order By: Relevance
“…It should also be observed that the permitted occupational exposure limit (OEL) to asbestos was progressively lowered in the last years [5] (p. 249) and [46].…”
Section: Laws On the Prevention Control And Compensation Of Asbestomentioning
confidence: 99%
See 2 more Smart Citations
“…It should also be observed that the permitted occupational exposure limit (OEL) to asbestos was progressively lowered in the last years [5] (p. 249) and [46].…”
Section: Laws On the Prevention Control And Compensation Of Asbestomentioning
confidence: 99%
“…clearly attributable to chrysotile exposure in Chinese studies than in mostly of the western studies with a prevalence of male smoker cohorts [5] (p. 250) and [30].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the global epidemiological situation of pneumoconiosis must be understood in order to develop an effective control strategy. Although many epidemiological studies of pneumoconiosis (e.g., Seaton et al, 1991;Linch et al, 1998;Kauppinen et al, 2000;Rosenman et al, 2003;Saiyed and Tiwari, 2004;Soutar et al, 2004;Carneiro et al, 2006;Smith and Leggat, 2006;Bang et al, 2008;Madl et al, 2008;Mazurek and Attfield, 2008;Choi et al, 2010;Laney et al, 2010;Nelson et al, 2010;Suarthana et al, 2011;Nelson, 2013), more than 20 articles about the epidemiological analysis of pneumoconiosis in domestic provinces and cities (e.g., Li et al, 2010;Courtice et al, 2012;Zhang et al, 2013;Mo et al, 2014), and 1 article from Changji, Xinjiang have been published in the last 5 years, there have been no reports about the epidemiological analysis of pneumoconiosis in the Xinjiang Uygur Autonomous Region or by the Urumqi Railway Bureau. Accordingly, to understand the epidemiological characteristics and dynamic changes of new cases of pneumoconiosis in Xinjiang in recent years, this epidemiological study investigated pneumoconiosis cases before June 2006 and from July 2006 through 2010 in the Xinjiang Uygur Autonomous Region as well as cases reported by the Urumqi Railway Bureau from 1981 to 2012.…”
Section: Introductionmentioning
confidence: 99%
“…In China, the estimated number of workers exposed to asbestos was one million [2], and the excess mortality for these population might be substantial [3]. In face of the substantial burden of non-malignant and malignant asbestos-related diseases (ARDs), new molecular biomarkers for screening the subjects with high risk of developing ARDs are undoubtedly needed.…”
Section: Introductionmentioning
confidence: 99%